Two new species of Weinmannia (Cunoniaceae) from Machu Picchu and Oxapampa, Peru - Arroyo, Frank (Phytotaxa, 2021)
Weinmannia machupicchuensis and W. oxapampana, two endangered species of Cunoniaceae endemic to the montane forests of the Peruvian Andes are newly described and illustrated. Data on ecology and their relationships with similar species are also discussed.